Three-dimensional Thermodynamic Structures of the Intracluster Medium across Edges in the X-Ray Surface Brightness of Massive, Bright, Dynamically Active Galaxy Clusters - Shutaro Ueda; Yuto Ichinohe (The Astrophysical Journal, 2024)
We present a detailed study of three-dimensional (3D) thermodynamic structures of the intracluster medium (ICM) across edges in the X-ray surface brightness of four massive, bright, dynamically active galaxy clusters (A3667, A2319, A520, and A2146), with the Chandra X-ray Observatory. Based on a forward modeling approach developed in previous work, we extend this approach with more generalized ICM density and temperature profiles, allowing us to apply uniformly to the observed X-ray surface brightness profiles to detect edges and measure the 3D thermodynamic profiles of the ICM simultaneously and self-consistently. With the forward modeling analysis, we find, in agreement with previous works, that the obtained 3D thermodynamic structures of the ICM across the edges in A3667 and A2319 are consistent with the characteristics of cold fronts, whereas those in A520 and A2146 are consistent with the nature of shock fronts. We find that the azimuthal distribution of the pressure ratio at the cold front in A3667 shows a different trend from that in A2319. For the shock fronts in A520 and A2146, the observed 3D temperature profiles of the ICM indicate that the temperature is highest at the position of the shock front. In the case of the sector exhibiting ${ \mathcal M }=2.4$ in A520, the ICM temperature appears isothermal with a temperature of ∼10 keV until ∼300 kpc away from the shock front in the post-shock region, being consistent with the hypothesis of the instant-equilibration model for shock heating.